My beloved world [compact disc, unabridged] - Sotomayor, Sonia, 1954- (Random House Audio, 2013)
The first Hispanic and third woman appointed to the United States Supreme Court, Sonia Sotomayor has become an instant American icon. Now, with a candor and intimacy never undertaken by a sitting Justice, she recounts her life from a Bronx housing project to the federal bench, a journey that offers an inspiring testament to her own extraordinary determination and the power of believing in oneself.